ISSUES OF THE ELEMENTS OF THE CLAIM FOR CONFISCATION OF PROPERTY OF ILLICIT ORIGIN IN THE CIVIL PROCEEDINGS OF RA - Khachatryan, Meri (State and Law, 2022)
Due to the specifics of the proceedings for confiscation of property of illicit origin, the elements of the claim presented in such proceedings have a differentiated manifestation. In the context of the practical significance, the criteria for the individualization of the claim of confiscation of property of illegal origin were presented in the context of the precedent decisions of the Court of Cassation RA. The article highlighted the characteristics of the claim for confiscation of property of illegal origin and the means of its distinctions. The precise determination of the scope of the factual circumstances of the claim is of a great importance in the context of determining the burden of proof and evaluating the justification of the claim. In the article, the grounds for initiating a lawsuit and the factual circumstances underlying the claim were studied, on the basis of which their differences were highlighted. It is essential to emphasize that a claim under the Law on Confiscation of Illegally Acquired Property should not only include facts that fail to justify the acquisition of property with legal income but also establish the connection between the acquisition of such property and criminal activity, aligning with the objectives set forth by the Law. Considering the fact that such claims are a novelty in judicial practice, the conclusions made in the article can be a guideline for law enforcement practice.
Keywords: claim for confiscation of property of illicit origin; basis of a claim; object of а claim; investigation of the grounds for initiating a claim; means of individualization of a claim; the authorized body; an in rem claim